The impact of PROGRESA on health: final report - Gertler, Paul (International Food Policy Research Institute, 2000)
In this paper, we investigate the impact of a unique anti-poverty program in Mexico on health. The program, PROGRESA, combines a traditional cash transfer program with financial incentives for families to invest in the human capital (health, education and nutrition). Program benefits include cash transfers that are disbursed conditional on the household engaging in a set of behaviors designed to improve health and nutrition. The family only receives the cash transfer if: (i) every family member accepts preventive health services; (ii) children age 0-5 and lactating mothers attend nutrition monitoring clinics where their growth is measured, they obtain nutrition supplements, and they receive education on nutrition and hygiene; and (iii) pregnant women visit clinics to obtain prenatal care, nutritional supplements, and health education. Our analysis takes advantage of a controlled randomized design. In 1998, 506 of the 50,000 PROGRESA villages were randomly assigned to control and treatment groups. Eligible households in treatment villages received benefits immediately, while benefits for eligible households in control villages were postponed until after the year 2000. A pre-intervention baseline survey of approximately 19,000 households with over 95,000 individuals and four follow-up surveys (at six month intervals) of the same households were conducted over the two-year experimental period. We find that the program significantly increased utilization of public health clinics for preventive care including prenatal care, child nutrition monitoring, and adult checkups. The program also lowered the number of inpatient hospitalizations, which is consistent with the hypothesis that PROGESA lowered the incidence of severe illness. Moreover, there was no reduction in the utilization of private providers, suggesting that the increase in utilization at public clinics was not substituting public care for private care. More importantly we find a significant improvement in the health of both children and adults.